Within-tree and between-tree variation of wood density components in cork oak trees in two sites in Portugal - Knapic, Sofia (2019)
The axial and radial variation of wood density was studied using microdensitometry in cork oaks ( Quercus suber ) in two sites in Portugal. The observations were made in mature trees under cork production and in juvenile trees before the fi rst cork extraction, at three height levels (stem base, 1.3 m and before stem bifurcation). The cork oak wood revealed a very high mean density (0.884 – 1.068 g cm 3 ). Differences between earlywood and latewood were small (0.866 and 1.061 g cm 3 , respectively). Latewood corresponded on average to 61 per cent of the total. The variation of density between trees was statistically highly signifi cant, but no differences were found between the two sites. The within-tree axial variation was negligible but the radial direction within a cross-section was one of the main origins of variation of the density components (18 per cent of the total variation). The density decreased from pith to cambium and this radial variation corresponded to 19 – 24 per cent of the total variation of wood density. Overall, the magnitude of density variations between and within cork oaks was small and an advantageous factor for their use for quality wood products